Wear behavior of AA1060 reinforced with alumina under different loads - Rosenberger, Mario Roberto (2009)
The wear behavior of samples of AA1060 aluminum matrix reinforced with 15 vol% of alumina particles in a range of loads between 4.9 and 91.2 N was determined using a pin-on-ring machine at a velocity of 2.7 m/s. The counterface was a carbon steel ring of 272 HB in hardness. Optical and electronic microscopy, X-ray energy analysis and hardness measurement were performed in order to characterize the worn samples. A mild wear mechanism is present for loads lower than 80 N and at larger loads the mechanisms change to a severe mode. In the mild wear regime a mechanically mixed layer (MML), with iron from the counterface and material of the composite, was formed. This MML was responsible of the wear resistance of the composite. Two mechanisms were observed as a way to increase the resistance of the MML; first hardening by mechanical alloying and strain hardening, and then an increase in thickness. At a larger load the conditions produced large instabilities which prevented the formation of a protective mechanically mixed layer. © 2008 Elsevier B.V. All rights reserved.